Civic Literacy Strengthening Through Curriculum and Community Synergy: Penguatan Literasi Kewarganegaraan Melalui Sinergi Kurikulum dan Komunitas - Arthaningsih, Ni Kadek Juni; Sanjaya, Dewa Bagus; Suastika, I Nengah (Pedagogia : Jurnal Pendidikan, 2025)
The enhancement of civic literacy at the elementary school level has become essential amid globalization and technological advancement. This study aimed to examine the implementation of civic literacy movements through a literature review approach. The method used involved reviewing relevant studies and policy documents. The findings revealed that civic literacy can be strengthened through curriculum integration, active teacher roles, school-based literacy programs, and community support. Effective strategies include contextual learning approaches, character value reinforcement, and cross-sector collaboration. This study concludes that the civic literacy movement plays a crucial role in shaping students into critical, participatory, and character-driven citizens. Highlights: Enhancing civic literacy prepares students to face globalization and technology. Integration in curriculum and teacher involvement are key strategies. Collaboration among schools, communities, and sectors strengthens outcomes. Keywords: Civic Literacy, Primary Education, Curriculum Integration, Character Education, Globalization